Characterizing gibberellin flow in planta using photocaged gibberellins. Issue 5 (29th November 2018) - Wexler, Shira; Schayek, Hilla; Rajendar, Kandhikonda; Tal, Iris; Shani, Eilon; Meroz, Yasmine; Dobrovetsky, Roman; Weinstain, Roy
Abstract : We report on novel photocaged gibberellins that provide a unique platform to study gibberellin movement in living, intact plants. Abstract : Gibberellins (GAs) are ubiquitous plant hormones that coordinate central developmental and adaptive growth processes in plants. Accurate movement of GAs throughout the plant from their sources to their destination sites is emerging to be a highly regulated and directed process. We report on the development of novel photocaged gibberellins that, in combination with a genetically encoded GA-response marker, provide a unique platform to study GA movement at high-resolution, in real time and in living, intact plants. By applying this platform to the Arabidopsis thaliana endogenous bioactive gibberellin GA4, we measure kinetic parameters of its flow, such as decay length and velocity, in vivo .